Controle alternativo do tripes-rajado, Corynothrips stenopterus Williams, com produtos naturais, a base de fitoquímicos, na cultura da mandioca em Itacoatiara-AM - Melo, Edvam Gama de (Brasil, 2024)
Abstract: Cassava accounts for more than half of the agricultural area in Amazonas. The municipality of Itacoatiara has a yield of 12 tons/ha, around 3 tons less than the national average. One of the reasons for this low productivity is pests, which can cause yield losses of between 5 and 88%. Among the pests of the crop in the municipality is the thrips, Corynothrips stenopterus (Williams). However, there is no registered product available to control this pest. The aim of this study was to evaluate the efficiency of alternative control using natural insecticides to control thrips in cassava. The products tested were 5% ethanolic extracts of Piper aduncum L. (Piperaceae) and neem, Azadirachta indica A. Juss. Juss. (Meliaceae), as well as the solvent ethanol and the control with distilled water. The experiment was organized in four blocks of five plots, with two to three plants/plot and conducted in a group of experiments, with two trials. Insects were sampled on 4 leaves/plant before and after spraying. Based on this data, the efficacy of each product was established and submitted to ANOVA and compared using Duncan's test. The two extracts were efficient and did not differ from each other, with a maximum efficiency of 28.4%. With this maximum level of efficiency, the products should not be used in isolation as the only method of control, especially when the thrips infestation is very high. It is recommended that tests be carried out with the concentrated crude extract, evaluating higher doses of the botanical active ingredient.